PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT. KALBE FARMA, TBK PERIODE 2014-2023 - Shakira, Mayang; Khoiriah, Neneng (Journal of Research and Publication Innovation, 2024)
This research aims to determine whether there is an influence of the Current Ratio and Debt to Equity Ratio on Return On Assets at PT. Kalbe Farma, Tbk for the period 2014-2023. The method used in this research is a quantitative method. Data analysis uses analysis: descriptive statistical analysis, Classic Assumption Test, Multiple Linear Regression Test, Hypothesis Test, Correlation Coefficient Test (R), and Determination Coefficient Test (R2). Using the SPSS 26 application. Based on the results of research conducted, the Liquidity Ratio Variable (Current Ratio) was partially proven to have no effect on Return On Assets based on tcount < ttable (-1,567 < 2.365) with a significant value of 0.161 > 0.05. The Debt to Equity Ratio variable has been partially proven to have no effect on Return On Assets based on tcount < ttable (2.120 < 2.365) with a significant value of 0.072 > 0.05. The variables Current Ratio (X1) and Debt to Equity Ratio (X2) are simultaneously proven to influence Return On Assets (Y) based on Fcount > Ftable (5.109 > 4.74) with a significant value of 0.43 > 0.05. The results of the coefficient of determination test show that the Adjusted R Square value is 59.3% of Return On Assets (ROA), while the remaining 40.7% is influenced by other variables not examined in this research.